2014
DOI: 10.1155/2014/832947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protective Resin Coating on the Surface Roughness and Color Stability of Resin-Based Restorative Materials

Abstract: The aim of this study was to evaluate the effects of nanofilled protective resin coating (RC) on the surface roughness (Ra) and color stability (ΔE) of resin-based restorative materials (RM) (compomer (C), nanofilled composite (NF), and microhybrid composite (MH)) after being submitted to the ultraviolet aging (UV) method. Thirty-six specimens were prepared (n = 6 for each group). The Ra and (ΔE) values and SEM images were obtained before and after UV. Significant interactions were found among the RM-RC-UV pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(59 reference statements)
2
13
1
1
Order By: Relevance
“…This result is in agreement with previous studies 13,14) . Hydrophobic materials such as resins are believed to exhibit greater stain resistance and color stability than hydrophilic materials 13,15,16) .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is in agreement with previous studies 13,14) . Hydrophobic materials such as resins are believed to exhibit greater stain resistance and color stability than hydrophilic materials 13,15,16) .…”
Section: Discussionsupporting
confidence: 94%
“…It was also reported that the resin-coated samples had significantly higher R a values than the control group after UV aging for both the compomer and the composite. Bagis et al 14) believed that higher and clinically unacceptable Ra values after UV aging might be related to the aging method that was used in their study. In the current study, there were no differences among the polishing systems and restorative material groups on the surface roughness after staining and thus second null hypothesis of the study was accepted.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Acid-etch technique was introduced by Buonocore in 1955, later in 1956, Bowen introduced resin Composites ( 1 , 2 ). The development of resin composites has led to the inclusion of aesthetic aspects of dental direct restorations and met the demands of patients who are not only expecting a dentist to reconstruct their teeth with their restorative materials, but also require restorations that are tooth-colored and not detectable ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating surface roughness is important to predict the longevity of the restoration. Higher surface roughness represents a risk factor for accumulation of plaque and stains on dental restoration which in turn may affect friction, wear and optical properties of the restoration (4,10,11,(20)(21)(22)(23)(24)(25) .…”
Section: Introductionmentioning
confidence: 99%